Rancang Bangun Sistem Informasi Pertanahan Desa Randu Padangan Kec. Menganti Kab. Gresik - Hasyim, Wachid; Setyawan, Henry Bambang; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Randu Padangan village is one of the villages in Gresik Regency which has a population of approximately 4500 inhabitants and many farm fields and plantations. With increasing population led to the need for land for settlement increased and many citizens who sell and buy land for the necessities of life. Related to it Governance in particular village government party in charge of handling and serving information land experiencing difficulties in terms of land information services. It looks at the data search process a very long land until it reaches 2 days and the presentation of data on land that is still difficult to understand especially on imagemap map data blocks with the current data block is still separate. This led to theinformation given to the citizens of less accurate. Based on the problems described previously the village of Randu Padangan requires a land information system that can assist the Government in conducting logging landand provide information that is accurate and speedy land to citizens. The results showed that Randu Padangan Village Land information systems can assistthe Government in conducting land and logging provides information on defense, so the  land information service can be quickly solved with accurate and timely.